An Examination of Nepal’s Export Choice based on Revealed Comparative Advantage - Salike, Nimesh; Lu, Benli (NRB Economic Review, 2015)
This paper examines the comparative advantage of a selection of 27 Nepal’s export products, of which 16 are extracted from the Nepal Trade Integration Strategy (NTIS 2010) list of potential priority exports. The primary purpose of this study is to investigate if these priority export products are in alignment with the concept of comparative advantage. Balassa’s revealed comparative advantage (RCA) index is used as the methodology for analysis while the data used spans from 2000 to 2011. Empirical results show that out of the 16 NTIS 2010 potential priority exports, only 10 are products which Nepal has comparative advantage in producing, major ones being pashmina, wool and agro food products. The findings also reveal that there are at least three other products- carpets, textile and juice that Nepal poses high RCA indices but are not included under NTIS 2010 priority list.